Application of Z-Numbers for Evaluation and Aggregation of the Travel Threats in the Post-Pandemic Era - Nuriyev, Aziz (European Journal of Social Science Education and Research, 2024)
The purpose of this paper is a study of the applicability and efficiency of the Z-numbers (Zadeh, 2011) for estimation of the various travel risk factors, aggregation, and evaluation of the overall risks of the different destinations.  At present, travel risk analysis is mainly carried out by using the available statistical data about target country. Therefore, the possibilities of analysing the risks of travelling to a country/region, with insufficient or unreliable information remain questionable. Moreover, the sharp decline of the number of tourists travels due to the COVID-19 pandemic could lead to a decrease of the amount of necessary statistic data. To improve quality of the risk assessment, especial in post-pandemic era, the procedures of the Z-numbers based risks identification, assessment and risks aggregation are suggested. Expert’s predictions of the risks are formalized as Z-number-based evaluations. This approach allows considering reliability of the information. For aggregation of the tourist threats of different nature, the method for calculation of Z-weighted arithmetic means was proposed, the overall risk was determined by aggregating factors and a riskier direction was identified. Suggested approach provided an opportunity to go beyond the country-specific statistic-based risk assessment. Tourism risks assessment by using of Z-numbers as well as the proposed method of risks aggregation allows to conduct a comparative analysis of the risks, travelling to different destinations, even in conditions of large uncertainty.
Keywords: travel threats, risk factors, Z-number-based evaluation, risk aggregation, Z-weighted arithmetic means